Neighbour effects on shrub seedling establishment override climate change impacts in a Mediterranean community. (26th November 2015) - Rysavy, Anne; Seifan, Merav; Sternberg, Marcelo; Tielbörger, Katja
Abstract: Questions: Can theory about plant–plant interactions along climate gradients help us predict how climate change will affect shrub establishment? How does a predicted reduction in rainfall affect the outcome of the interactions between shrub seedlings and herbaceous plants in a dryland ecosystem? Location: Three field sites along a rainfall gradient and an adjacent experimental site at the Botanical Gardens of Tel Aviv University, Israel. Method: We measured seedling survival of a dominant shrub species in response to the presence of herbaceous neighbours and to rainfall amount using two approaches: First, we employed a space‐for‐time approach and studied seedling survival along an aridity gradient that was shown to mimic the predicted rainfall changes. Second, we monitored seedling survival in a common garden experiment in which we simulated drought using rainout shelters. In both experiments we contrasted the importance of water availability relative to the presence of herbaceous neighbours and the origin of the shrub seedlings. Results: Our results showed that neighbours always had a negative effect on shrub seedling survival. In contrast to theoretical predictions, the intensity of competition increased with reduction in water availability. Shrub seedlings originating from drier conditions showed higher survival than seedlings from mesic origin. Conclusions: These results emphasize the importance of incorporating biotic interactions in studies predicting changes in plant dynamics under climate change. Moreover, plant species growing in ecosystems prone to high rainfall variability showed a greater ability to cope with dry conditions, which suggests more nuanced origin‐specific predictions than suggested by recent climate models. Abstract : A field and garden experimental set‐up enabled us to assess the potential impact of neighboring plants on shrub seedling establishment under different climate change scenarios. Our results emphasize the importance of incorporating biotic interactions into climate‐change models as the ability of the shrubs to cope with the drier conditions was strongly affected by the presence of neighbors and their origin.